Study of Public Perceptions on the Urban Railway Planning of the City of Banda Aceh and the Surrounding Areas - Sofyan M Saleh; Diana Devi; Muhajir Muhajir; Rizal Rinaldi; Salsabila Ashfa; Muhammad Ahlan; Yusria Darma (Aceh International Journal of Science and Technology, 2022)
The urban railway in the City of Banda Aceh and the surrounding areas is currently being proposed by the Aceh Provincial Government through the Department of Transportation of Indonesia. The presence of this rail transport mode is expected to change the travel behavior of the commuter. As such, people who use private vehicles may shift to public transport mode, thereby reducing congestion, noise, and pollution. The objective of this study is to determine factors and indicators—related to rail transport—that are important to the community. This study was conducted to provide information on the urban railway planning of the City of Banda Aceh. The principal component analysis (PCA) was utilized in this study. The results analysis of the study shows that the most significant variable influencing the public on the urban railway for Banda Aceh City is land use (19.09%). The indicator that is important to the community under the land use factor includes the property used as railway (0.911), land use used as railway (0.907), adjacent land used as railway infrastructure (0.876), and adjacent property used as railway infrastructure (0.861). Overall, the respondents positively perceived the urban railway planning of Banda Aceh City and accepted the city's rail transport plan.